Analisis Pengaruh Kualitas Pelayanan Publik Terhadap Kepuasan Masyarakat (Studi tentang Layanan Perizinan Online Pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kabupaten Badung) - Anak Agung Sagung Putri Nidyasari; Kadek Wiwin Dwi Wismayanti; Ni Putu Anik Prabawati (CV. Lenggogeni Data Publishing, 2023)
Community satisfaction is the result of community opinions and assessments of the performance of services provided by public service providers. Public satisfaction reflects the government's success in providing effective and efficient public services. The factor that can influence the level of public satisfaction is the quality of public services. This research aims to analyze the influence of the quality of LAPERON public services in DPMPTSP Badung Regency on the satisfaction of people using LAPERON. This research was conducted on LAPERON users with a sample size of 370 respondents. Data collection in this research was carried out using the questionnaire method. The data analysis techniques used in this research are Simple Linear Regression Test, Simple Correlation Test, Determination Test, and T Test. The results of this research correlation test get a score of 0.855, so it can be said that variables X and Y have a very strong correlation. Then the results of the coefficient of determination, namely by squaring the correlation results, produce an R-Square of 0.731, which means that the quality of public services has an influence on public satisfaction of 73.1%. So it can be concluded that H0 is rejected and H1 is accepted. There is a positive and significant influence between the quality of LAPERON public services in DPMPTSP Badung Regency on the satisfaction of the LAPERON user community. The advice for LAPERON in DPMPTSP Badung Regency is to continue to pay attention to the quality of public services so that they remain positive, which can increase public trust and satisfaction with LAPERON.